(untitled) (Journal of Asian Development Studies, 2025)
Celebrity endorsement is one of the most well-known marketing strategies. It is regarded as a successful tactic for creating a distinctive brand identity. When selecting a celebrity, a number of things need to be taken into account. Finding the right celebrity is a difficult undertaking, but matching the celebrity with the brand is much more difficult. Keeping this in mind the goal of the current study was to determine how celebrity endorsements affect a number of factors, such as attitude towards luxury brands, perceived quality, brand loyalty and purchase intention of luxury brands. We learnt about the changing aspects and complications of the market within the youth in context. 130 individuals in all responded our survey, adding to the hypothetical and practical discussions. The importance and value of celebrity endorsements as an analytical tool is highlighted by our findings, which demonstrated an inverse relation between dependent and independent variables. These insights enabled us to offer conclusions and recommendations by optimizing the process of integrating research findings with practical methods. Additionally, we observed that adequate celebrity endorsement can have a significant positive effect on the marketing of luxury brands.